2014 IEEE Seventh International Conference on Software Testing, Verification and Validation 2014
DOI: 10.1109/icst.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

SimLatte: A Framework to Support Testing for Worst-Case Interrupt Latencies in Embedded Software

Abstract: Embedded systems tend to be interrupt-driven, yet the presence of interrupts can affect system dependability because there can be delays in servicing interrupts. Such delays can occur when multiple interrupt service routines and interrupts of different priorities compete for resources on a given CPU. For this reason, researchers have sought approaches by which to estimate worst-case interrupt latencies (WCILs) for systems. Most existing approaches, however, are based on static analysis. In this paper, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The number of events N to be issued is generated in terms of the specified event density. Our previous work [56] also showed that appropriately adjusting interrupt density can enhance testing effectiveness. Based on our empirical observations for the object programs (Section 4), SIMEXPLORER chooses the interrupt density to be 60%; ie, the system spends 60% of its instruction cycles executing interrupt handlers.…”
Section: Variables and Measuresmentioning
confidence: 99%
“…The number of events N to be issued is generated in terms of the specified event density. Our previous work [56] also showed that appropriately adjusting interrupt density can enhance testing effectiveness. Based on our empirical observations for the object programs (Section 4), SIMEXPLORER chooses the interrupt density to be 60%; ie, the system spends 60% of its instruction cycles executing interrupt handlers.…”
Section: Variables and Measuresmentioning
confidence: 99%
“…Automated test generation using search based testing techniques are described by [14] for testing worst case interrupt latencies in embedded systems. Further surveys in [15] confirms its application being extended to other non functional system attributes like safety [16], usability, quality of service [17] and security [18].…”
Section: Related Workmentioning
confidence: 99%
“…This article draws on two previously published conference papers , in which we proposed initial algorithms to detect WCILs and WCSUs. We have extended that work substantially by considering WCETs.…”
Section: Introductionmentioning
confidence: 99%
“…We have extended that work substantially by considering WCETs. We have also extended our work on WCILs to use a hybrid algorithm, whereas in Yu et al , we used only a GA. Finally, we have performed a larger empirical study on a more substantial base of artefacts and have generalized our approach into a framework resulting in a number of changes to both the presentation of the article along with detailed descriptions of the algorithm, evaluation, and related work.…”
Section: Introductionmentioning
confidence: 99%